PENGARUH PERPUSTAKAAN PERGURUAN TINGGI DALAM MENGEMBANGKAN BUDAYA LITERASI DIGITAL MAHASISWA ILMU PERPUSTAKAAN DAN INFORMASI ISLAM UIN RADEN MAS SAID SURAKARTA: PENGARUH DAN HUBUNGANNYA - Alifia Rachma Aghan; Filda Tria Devita; Mega Alif Marintan (Vol. 3 No. 2 (2025): Special Issue: Cultural Resilience and Digital Literacy for a Diverse Society)
The development of technology and information at this time has a significant influence on digital literacy, particularly for students. Therefore, this study aims to investigate the impact of university libraries on developing a digital literacy culture among students in the Islamic Library and Information Science Study Program at UIN Raden Mas Said Surakarta. The research used a descriptive quantitative method. Data collection techniques were employed through questionnaires, observation, and documentation, involving 65 students from a total of 180 students in the Islamic Library and Information Science study program. The results of this study demonstrate that the role of university libraries is highly influential in shaping students' literacy culture. However, students still face several obstacles, including inadequate web access, a lack of understanding of digital services, and limited promotion and socialization. Therefore, it is essential to establish a culture of digital literacy in college libraries to support and meet the academic needs of students.